PTU-253 The development of a bsg/acpgbi minimum dataset proforma for the multidisciplinary assessment and management of large nonpedunculated colorectal polyps. (22nd June 2015) - Chattree, A; Barbour, J; Dolwani, S; Rutter, MD
Abstract : Introduction: The lack of a structured framework for the assessment and management of large non-pedunculated colorectal polyps (LNPCPs) appears to have resulted in a wide variation in decision making with regards to endoscopic and surgical management and suboptimal outcomes. 1 Multidisciplinary team discussion has been advocated to better coordinate management. The development of an evidence based and expert approved minimum dataset proforma may complement this process and encourage optimal management resulting in improved outcomes. Method: Following an extensive literature review, various patient and polyp parameters relevant to LNPCP assessment and management were selected. A 14 person BSG/ACPGBI approved multidisciplinary panel participated in Delphi consensus methodology to vote anonymously on the proposed parameters with ≥80% agreement required for consensus to be achieved. The draft proforma was then assessed on a sample of 20 LNPCP cases, resulting in modification after a further voting round. Results: The final proforma comprised of 17 parameters encompassing all patient and lesion factors considered essential to the decision making process in LNPCP management. Patient parameters included patient symptoms, treatment preferences and comorbidity. Lesion parameters included morphology and surface characteristics (e.g. Paris classifications and Pit pattern) and the specification of any lesion features associated with increased complexity such an increased risk of malignancy, unsuccessful endoscopic resection or adverse endoscopic events. 2 Parameters regarding relevant histology and radiology results and guidance on obtaining adequate lesion imaging were also agreed. Conclusion: The development and validation of a BSG/ACPGBI minimum dataset proforma allows for structured and comprehensive multidisciplinary discussion in LNPCP management, ensuring that all important factors are discussed and resulting in more coordinated and robust decision-making. This proforma can be used to structure discussions during a multidisciplinary team meeting and all related discussions such as referral to the tertiary setting, in addition to being used as a checklist for comprehensive lesion assessment. Disclosure of interest: None Declared. References: Lee TJ, Rees CJ, Nickerson C, et al . Management of large sessile or flat colonic polyps in the English bowel cancer screening programme. Br J Surg. 2013;100:1633–9 Moss A, Bourke MJ, Williams SJ, et al . Endoscopic mucosal resection outcomes and prediction of submucosal cancer from advanced colonic mucosal neoplasia. Gastroenterology 2011;140:1909–18